Foreign Body (Bamboo Splinter of Broom Stick) in Soft Tissue - Pramanik, MA Kasem; Bhaduri, Joydeep; Rashid, AM; Hasan, M Nazmul (TAJ: Journal of Teachers Association, 2009)
Patients with foreign bodies inside soft tissues are common in a surgeon's daily practice,. Radio-opaque foreign bodies can easily be located with radiography but radio-lucent foreign bodies cannot be located with X-ray, where Ultrasonography especially, high resolution ultrasonography can be used to locate it. Ultrasonography, being easily available, cost-effective and radiation-hazard free, can be done repeatedly for foreign bodies which move inside tissues. The presenting article describes a patient with a radio-lucent foreign body, deep inside muscle in his fore-arm and having one sharp end, was advancing inside tissues, was located with the help of Ultrasonography and was removed. doi: 10.3329/taj.v20i1.3095 TAJ 2007; 20(1): 67-70